Une brève histoire des communautés noires du Canada - Voltaire, Frantz (Centre International de Documentation et d'Information Haïtienne, Caribéenne et Afro-canadienne, 2007)
Keywords: Noirs

Le SIDA et la discrimination envers la population noire de Montréal - Gélineau, Lucie (Université de Montréal, 1988)
Keywords: Noirs

La présence des Noirs dans la société québécoise d'hier et d'aujourd'hui - La Grenade-Meunier, Monique; Fehmiu Brown, Paul (Ministère des Affaires internationales, de l'Immigration et des Communautés culturelles et ministère de l'Éducation, 1995)
Keywords: Noirs

Nègres noirs, Nègres blancs. Race, sexe et politique dans les années 1960 à Montréal - Austin, David (Lux Éditeur, 2015)
Translators: _:n45006
Keywords: Noirs

Les Noirs et le jazz au Québec - Lelièvre, Denys (Cap-aux-Diamants, 2004)
issued: 2004-23-00
Keywords: Musique; Noirs

Histoire des communautés noires au Québec et à Montréal (3e partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
issued: 2020-23-00
Keywords: Haïtiens; Noirs

Des noirs sous un voile blanc: métissage et abolition tranquille de l’esclavage - Mackey, Frank (Cap-aux-Diamants, 2017)
issued: 2017-22-00
Keywords: Esclaves; Noirs

La présence des Noirs au Québec: état des lieux et examen de quatre manuels d'enseignement de l'histoire au XIXe siècle - D'Almeida, Augustin Roland (Université Laval, 2010)
Keywords: Histoire; Noirs

" J’ai vécu des années dans la proximité des Noirs ": Louis Dantin, Stanley et Frances Fields-Johnston – amitié, amour et littérature - Aubé, Mélanie; Hébert, Pierre (Quebec Studies, 2019)
issued: 2019-21-00/2019-22-00
Keywords: Noirs; Poésie; Écrivains

Histoire des communautés noires au Québec et à Montréal (2e partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
issued: 2020-22-00
Keywords: Chemins de fer; Musique; Noirs; Travail

L’école québécoise assure-t-elle l’égalité des chances? Le cheminement scolaire des jeunes noirs au secondaire - Mc Andrew, Mary; Ledent, Jacques; Ait-Said, Rachid (Cahiers québécois de démographie, 2006)
issued: 2006-21-00
Keywords: Africains; Anglophones; Caribéens; Francophones; Noirs

Sankofa: Recovering Montreal’s Heterogeneous Black Print Serials - Williams, Dorothy W. (Université McGill, 2006)
Keywords: Noirs

Blacks in Québec Society, Past and Present - La Grenade-Meunier, Monique; Fehmiu Brown, Paul (Ministère des Affaires internationales, de l'Immigration et des Communautés culturelles et ministère de l'Éducation, 1995)
Keywords: Noirs

Black then: Blacks and Montreal, 1780-1880's - Mackey, Frank (McGill-Queen's University Press, 2004)
Keywords: Noirs

Blacks in Montreal, 1628-1986: An Urban Demography - Williams, Dorothy W. (Éditions Yvon Blais, 1989)
Keywords: Noirs

The Occupational Adjustments of Montreal Negroes, 1941-1948 - Potter, Harold Herbert (Université McGill, 1949)
Keywords: Noirs

The Montreal Negro Community - Israel, Wilfrid Emerson (Université McGill, 1928)
Keywords: Noirs

Fear of a Black Nation: Race, Sex, and Security in Sixties Montreal - Austin, David (Between the Lines, 2013)
Keywords: Noirs

The Road to Now: A History of Blacks in Montreal - Williams, Dorothy W. (Véhicule Press, 1997)
Keywords: Noirs

Blackness, exclusion, and the law in the history of Canada’s public schools, Ontario and Québec, 1850–present - Zellars, Rachel (Université McGill, 2017)
Keywords: Noirs

Afro-Canadian Activism in the 1960s - Stamadianos, Peter (Université Concordia, 1994)
Afro-Canadian activism became increasingly militant in the 1960s. The rise in militancy in the Afro-American leadership of the 1960s was one factor contributing to the new era of black politics in Canada. Increased immigration from the West Indies also encouraged the proliferation of Afro-Canadian organizations dedicated to challenging racial discrimination. Afro-Canadian activism, however, developed in a substantially different manner than black politics in the United States. On the whole, most Afro-Canadian organizations and leaders were considerably less militant in their tactics and strategies than their counterparts in the United States. Internecine divisions over ancestral origin were also more pronounced in Canada where the black population was ethnically heterogeneous when compared to the Afro-American community.
Keywords: Africains; Noirs

The Education of Black Students in Montreal Schools: an Emerging Anglophone Problem, a Non-Existent Francophone Preoccupation - Laferriere, Michel (Ethnic Canadians: Culture and Education, 1978)
Keywords: Noirs; Étudiants

Examining the Overrepresentation of Black Males in the Young Offender System - Johnson, Druscilla (Université McGill, 2000)
Keywords: Délinquance; Noirs

Toot Sweet: When Jazz Ruled Montreal - Reynolds, Mark (The Beaver, 2001)
issued: 2001-06/2001-07
Keywords: Musique; Noirs

Territorial Spoils, Transnational Black Resistance, and Canada's Evolving Autonomy during the First World War - Hastings, Paula (Histoire sociale / Social History, 2014)
Number: 94
Keywords: Caribéens; Noirs

Shadrach Minkins: From Fugitive Slave to Citizen - Collison, Gary (Harvard University Press, 1998)
Keywords: Esclaves; Noirs

Liberation from Below: the Caribbean Conference Committee of Montreal and the Global New Left - Austin, David (Université de Montréal, 2007)
Keywords: Caribéens; Noirs

In Search of Communal Identity: The Role of the Black Community in Identity Formation among Nigerian Youth - Ogbuagu, Buster C. (Université McGill, 2007)
Keywords: Nigériens; Noirs

Expressivité rituelle: corps et discours dans le culte dominical d'une église d'immigrants à Montréal - Mossière, Géraldine (Université de Montréal, 2004)
Keywords: Noirs; Églises

Le Black Theatre Workshop de Montréal: un nouveau bilan - Bayne, Clarence (L'annuaire théâtral, 2001)
issued: 2001-21-00
Keywords: Noirs; Théâtre

Race and beauty in Canada: print culture, retail, and the transnational flow of products, images and ideologies, 1700s to present - Thompson, Cheryl (Université McGill, 2014)
Keywords: Esclaves; Noirs

Étude de cas: <ì>The Free Lance - Williams, Dorothy (Histoire du livre et de l'imprimé au Canada, vol. III (1918-1980), 2004)
Keywords: Journalistes; Noirs

In the Free Lance - Williams, Dorothy (History of the book in Canada, vol. III (1918-1980), 2004)
OCLC: ocm54692696
Keywords: Journalistes; Noirs

La Maison d’Haïti: Haitian Stories of Resistance and Black Diasporic Activism in Montréal, 1972–1986 - Rochat, Désirée (Histoire sociale / Social History, 2022)
Keywords: Haïtiens; Noirs

Where They Stood: The Evolution of the Black Anglo Community in Montreal (Linda Leith Publlishing, 2023)
Keywords: Anglophones; Noirs

Notre Oscar Peterson est à New York - P. Boulianne, Sandria (Les médias parlent et chantent. Chroniques de la vie culturelle à Montréal durant la crise et la guerre, 2018)
Keywords: Musicien; Musique; Noirs

Femmes de soir (théâtre); suivi de Contours: réflexion à partir du théâtre africain-américain - Amoni, Emmanuelle (Université du Québec à Montréal, 2000)
Keywords: Africains; Noirs; Théâtre

The Role of the Black Community in Educating Blacks in Montreal, from 1910 to 1940, with Special Reference to Reverend Dr Charles Humphrey Este - Bertley, June A (Université McGill, 1982)
Keywords: Este; Charles Humphrey; Noirs

Locating Diasporas: Afro-Caribbean Migrations and the Transnational Dialectics of Race and Community in North America, 1910-1929 - Toney, Jared Glen (University of Toronto, 2014)
Keywords: Africains; Caribéens; Noirs

Hair 1970. La tribu métissée du Québec - Lavertu, Yves (Éditions Yves Lavertu, 2020)
Keywords: Musique; Noirs; Théâtre

Black Media in Montreal: In Defense of Abyssinia - Williams, Dorothy (Proceedings of the Seventh Annual History in the Making Conference: History and Media, Concordia University, March 2001, 2002)
Keywords: Esclaves; Journalistes; Noirs

Print and Black Canadian Culture - Williams, Dorothy (History of the Book in Canada, vol. II (1840-1918), 2004)
OCLC: ocm54692696
Keywords: Journalistes; Noirs; Écrivains

Jackie Robinson...Un Américain à Villeray - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2024)
issued: 2024-23-00
Keywords: Baseball; Noirs; Villeray

Montreal's Oldest Black Congregation: Union Church, 3007 Delisle Street - Bertley, Leo W. (Bilongo Publishers, 1976)
Keywords: Noirs; Union Church; Églises

The images produced by La Presse de Montréal of the Black community and crime - Albert, Sonia (Université de Montréal, 2006)
Keywords: Criminalité; Noirs; Presse (La)

Geographies and Futurities of Being: Radical Black Activism in a Context of Anti-Black Islamophobia in 1990s Montreal - Mugabo, Délice Igicari (Université Concordia, 2016)
Keywords: Groupes populaires; Musulmans; Noirs

Envisioning new futures: Portrait photographs of black Victorians in Montreal, 1861-1901 - Evoughlian, Sandra (Université McGill, 2018)
Keywords: Noirs; Notman; William; Photographie

Jackie Robinson, un été à Montréal: la fin de la ségrégation raciale dans le baseball - Dugas, Marcel (Hurtubise, 2019)
Keywords: Baseball; Noirs; Robinson; Jackie

Democracy, Dissent, and the City: Cross-Cultural Encounters in Sixties Montreal - Mills, Sean (The Sixties in Canada: a Turbulent and Creative Decade, 2009)
Keywords: Femmes; Féminisme; Noirs; Travail

La couverture médiatique du mouvement des droits civiques américain au Canada: analyse comparative de la presse anglo-canadienne et de la presse québécoise, 1960-1965 - Harvey Savard, Samuel (Université du Québec à Montréal, 2015)
Keywords: Devoir (Le); Noirs; Presse (La)

La voix des femmes: Haitian Women's Rights, National Politics and Black Activism in Port-au-Prince and Montreal, 1934-1986 - Sanders, Grace Louise (University of Michigan, 2013)
Keywords: Femmes; Féminisme; Haïtiens; Noirs

Antiracism organizing and resistance in nursing : African Canadian Women - Calliste, Agnes (Canadian Review of Sociology and Anthropology / Revue canadienne de sociologie et d'anthropologie, 1996)
Number: 3
Keywords: Africains; Femmes; Infirmières; Noirs

Jazz, gender, historiography: a case study of the "Golden Age" of jazz in Montreal (1925-1955) - Blais-Tremblay, Vanessa (Unviersité McGill, 2018)
Keywords: Femmes; Musicien; Musique; Noirs

Il fallait se défendre: l'histoire du premier gang de rue haïtien à Montréal - Aurélien, Maxime; Rutland, Ted (Mémoire d'encrier, 2023)
Keywords: Criminalité; Délinquance; Haïtiens; Noirs

Locating Crisis Representations of Race and Space in the English media, Montreal, 1987-1992 - Hadlaw, Janin (Université Concordia, 1996)
Keywords: Montreal Gazette; Noirs; Police; Télévision

The Universal Negro Improvement Association of Montreal, 1917-1979 - Bertley, Leo W. (Université Concordia, 1980)
Keywords: Noirs; Universal Negro Improvement Association of Montreal

Ethical Gestures: Articulations of Black Life in Montreal's 1960s - Affan, Samah (Université Concordia, 2013)
Keywords: Noirs; Université Sir George Williams; Écrivains

All Roads Led to Montreal: Black Power, the Caribbean, and the Black Radical Tradition in Canada - Austin, David (The Journal of African American History, 2007)
issued: 2007-23-00
Keywords: Africains; Caribéens; Groupes populaires; Noirs

"For the Freedom of the Black People": Case Studies on the Universal Negro Improvement Association in Canada, 1900-1950 - Marano, Carla (University of Waterloo, 2018)
Keywords: Noirs; Universal Negro Improvement Association of Montreal

Montréal-Nord 1980-2000. Aspects sociaux - Dupont, Antonin (Il était une fois... Montréal-Nord, 2009)
issued: 2009-23-00
Keywords: Haïtiens; Montréal-Nord; Noirs; Quartiers

The Coloured Women's Club of Montreal, 1902-1940: African-Canadian Women Confronting Anti-Black Racism - Este, David; Sato, Christa; McKenna, Darcy (Canadian Social Work Review / Revue canadienne de service social, 2017)
Keywords: Clubs; Femmes; Groupes populaires; Noirs

"A Microcosm of the General Struggle": Black Thought and Activism in Montreal, 1960-1969 - Hebert, Paul C. (University of Michigan, 2015)
Keywords: Groupes populaires; Noirs; Université Sir George Williams

Racialized social relations in higher education: Black student and faculty experiences of a Canadian university - Hampton, Rosalind (Université McGill, 2017)
Keywords: McGill Daily; McGill; James; Noirs; Université McGill

Proud past, bright future - Moses, Maranda (Union United Church, 2008)
Keywords: Congrégationalistes; Noirs; Protestants; Église Unie; Églises

Little Burgundy: The Interwoven Histories of Race, Residence, and Work in Twentieth-Century Montreal - High, Steven (Urban History Review / Revue d'histoire urbaine, 2017)
issued: 2017-23-00
Keywords: Chemins de fer; Noirs; Petite-Bourgogne; Quartiers; Travail

The Jackie Robinson Myth: Social Mobility and Race in Montreal, 1920-1960 - Williams, Dorothy W. (Université Concordia, 1999)
Keywords: Enseignants; Lord; Gwen; Lord; Richard; Noirs; Robinson; Jackie

North of the Colour Line: Sleeping Car Porters and the Battle Against Jim Crow on Canadian Rails, 1880-1920 - Mathieu, Sarah-Jane (Saje) (Labour / Le travail, 2001)
Keywords: Chemins de fer; Noirs; Transport en commun; Travail

“Rising Strongly and Rapidly”: The Universal Negro Improvement Association in Canada, 1919-1940 - Marano, Carla (Canadian Historical Review, 2010)
Number: 2
Keywords: Africains; Caribéens; Noirs; Universal Negro Improvement Association of Montreal

René Lévesque et la francophonie africaine - Roy, Jean-Louis (René Lévesque et le monde, 2018)
Keywords: Africains; Francophones; Idéologies; Journalistes; Lévesque; René; Noirs

Savoirs créoles: leçons du sida pour l'histoire de Montréal - Namaste, Viviane (Mémoire d'encrier, 2019)
Keywords: Groupes populaires; Haïtiens; Histoire; Infirmières; Noirs; Épidémies

Chroniques de l'école secondaire Henri-Bourassa. L'école, reflet de la société - Blanchard, Nicole (Il était une fois... Montréal-Nord, 2019)
issued: 2019-22-00
Keywords: Anglophones; Femmes; Francophones; Haïtiens; Noirs; Étudiants

"Hotel Refuses Negro Nurse": Gloria Clarke Baylis and the Queen Elizabeth Hotel - Flynn, Karen (Bulletin canadien d'histoire de la médecine / Canadian Bulletin of Medical History, 2018)
issued: 2018-23-00
Keywords: Femmes; Hôtellerie; Infirmières; Noirs; Reine-Élizabeth (hôtel)

From Self-Discipline to Self-Realization: Emotion Management in the Montreal Race Riots of 1969 and 2008 - Richter, Steve (Université Concordia, 2011)
Keywords: Latino-Américains; Montréal-Nord; Noirs; Université Sir George Williams; Émeutes

There's No Place Like Home: Feminist Communities, Social Citizenship and (Un)Belonging in Montreal's Long Women's Movement, 1952-1992 - Ricci, Amanda (Université McGill, 2015)
Keywords: Anglophones; Autochtones; Femmes; Francophones; Féminisme; Haïtiens; Italiens; Noirs

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (McGill-Queen's University Press, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."–
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail

La Petite-Bourgone: bercail de l'industrie et quartier historique multiracial de Montréal - High, Steven (Bulletin de l'AQPI, 2022)
issued: 2022-22-00
Keywords: Anglophones; Canadien National; Francophones; Grand Tronc; Lachine (canal); Montreal Rolling Mills; Noirs; Petite-Bourgogne; Quartiers; Sainte-Cunégonde